Handbook of Wind Power Systems - Pardalos, Panos M.; Rebennack, Steffen; Pereira, Mario V. F.; Iliadis, Niko A.; Pappu, Vijay (Energy Systems,, 2013)
Wind power is currently considered as the fastest growing energy resource in the world. Technological advances and government subsidies have contributed in the rapid rise of Wind power systems. The Handbook on Wind Power Systems provides an overview on several aspects of wind power systems and is divided into four sections: optimization problems in wind power generation, grid integration of wind power systems, modeling, control and maintenance of wind facilities, and innovative wind energy generation. The chapters are contributed by experts working on different aspects of wind energy generation and conversion.